2015
DOI: 10.1186/s40779-015-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

Medical rescue of naval combat: challenges and future

Abstract: There has been no large-scale naval combat in the last 30 years. With the rapid development of battleships, weapons manufacturing and electronic technology, naval combat will present some new characteristics. Additionally, naval combat is facing unprecedented challenges. In this paper, we discuss the topic of medical rescue at sea: what challenges we face and what we could do. The contents discussed in this paper contain battlefield self-aid buddy care, clinical skills, organized health services, medical train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Studies have suggested that environmental space, 3 magnetic fields, 4 the shockwave of external forces, 5 etc can all have an impact on brain activities. The potential impacts include the damage to brain tissues caused by staying in a complex electromagnetic environment for a long time; the impact of long-term navigation operation in a closed space of a cabin on the cognitive ability of the brain; the brain damage caused by an underwater explosion shockwave of each station personnel of surface ships or underwater submarines during naval battle 6 ; and the impact of post-traumatic stress disorder in the battlefield on the mental state and combat effectiveness. 7 These unknown problems have put forward a large number of research topics that need to be answered to understanding the brain.…”
Section: Contentmentioning
confidence: 99%
“…Studies have suggested that environmental space, 3 magnetic fields, 4 the shockwave of external forces, 5 etc can all have an impact on brain activities. The potential impacts include the damage to brain tissues caused by staying in a complex electromagnetic environment for a long time; the impact of long-term navigation operation in a closed space of a cabin on the cognitive ability of the brain; the brain damage caused by an underwater explosion shockwave of each station personnel of surface ships or underwater submarines during naval battle 6 ; and the impact of post-traumatic stress disorder in the battlefield on the mental state and combat effectiveness. 7 These unknown problems have put forward a large number of research topics that need to be answered to understanding the brain.…”
Section: Contentmentioning
confidence: 99%